PRODUKSI KARBON AKTIF DARI BATUBARA BITUMINUS DENGAN AKTIVASI TUNGGAL H3PO4, KOMBINASI H3PO4-NH4HCO3, DAN TERMAL - Esthi Kusdarini; Agus Budianto; Desyana Ghafarunnisa (Reaktor, 2017)
Abstract ACTIVE CARBON PRODUCTION OF BITUMINOUS COAL WITH SINGLE ACTIVITY H3PO4, H3PO4 COMBINE WITH NH4HCO3, AND THERMAL. Bituminous coal has a good potential to be utilized as activated carbon because it has high carbon, which is between 54-86%. The purpose of research was to obtain moisture content data, ash content, volatile matter, fixed carbon, absorption of iodine (iodine), area surface and the volume of pore activated carbon. Another aim was to study the effect of reagent types and concentrations of H3PO4 reagent and NH4HCO3 reagent to the characteristics of the activated carbon. The study was conducted in six stages: 1) carbonization; 2) chemical activation; 3) neutralizing; 4) filtering; 5) activation in physics; and 6) cooling. The renewal of this study is the use of reagents combination H3PO4-NH4HCO3. The results showed that the active carbon which is activated by a combination of  H3PO4  reagent 2 M - NH4HCO3 reagent 2 M and  reagent H3PO4 reagent 2.5 M - reagent NH4HCO3 reagent 2.5 M have the best iodine. Activated carbon is activated using H3PO4 reagent 2 M - NH4HCO3 reagent  2 M containing 7.5% water content; ash content of 9,0%; volatile matter content of 43.3%, 40.2% fixed carbon, iodine 1238.544 mg/g. While activated carbon which is activated using H3PO4reagent 2.5 M - NH4HCO3 reagent 2.5 M contain 7.4% water content; ash content is about 10%; volatile matter content is 39.1%, fixed carbon is 43.5%, iodine 1238.544 mg/g,  surface area 86.213 m2/g, and pore volume 0.0733 cc/g. Keywords: perf activation; coal; bituminous; H3PO4; NH4HCO3; active carbon  Abstrak Batubara bituminus mempunyai potensi bagus untuk dimanfaatkan menjadi karbon aktif karena mempunyai kandungan karbon yang cukup tinggi, yaitu antara 54-86%. Tujuan penelitian adalah memperoleh data kadar air, kadar abu, kadar zat terbang, fixed carbon, daya serap terhadap iodium (bilangan iodin), luas permukaan, dan volume pori karbon aktif. Tujuan lainnya adalah mempelajari pengaruh jenis dan konsentrasi reagen H3PO4 dan NH4HCO3 terhadap karakteristik karbon aktif. Penelitian dilakukan dalam enam tahap : 1) karbonisasi; 2) aktivasi secara kimia; 3) penetralan;; 4) penyaringan; 5) aktivasi secara fisika; 6) pendinginan. Pembaharuan dalam penelitian ini adalah penggunaan kombinasi reagen H3PO4-NH4HCO3. Hasil penelitian menunjukkan bahwa karbon aktif yang diaktivasi dengan kombinasi reagen H3PO4  2 M - NH4HCO3 2 M dan H3PO4  2,5 M - NH4HCO3 2,5 M mempunyai bilangan iodin terbaik. Karbon aktif yang diaktivasi menggunakan reagen H3PO4  2 M - NH4HCO3 2 M mengandung kadar air 7,5%, kadar abu 9,0%, kadar zat terbang 43,3%, fixed carbon 40,2%, bilangan iodin 1238,544 mg/g. Sedangkan karbon aktif yang diaktivasi menggunakan reagen H3PO4  2,5 M - NH4HCO3 2,5 M mengandung kadar air 7,4%, kadar abu 10%, kadar zat terbang 39,1%, fixed carbon 43,5%, bilangan iodin 1238,544 mg/g, luas permukaan 86,213 m2/g, dan volume pori 0,0733 cc/g. Kata kunci: aktivasi; batubara; bituminus; H3PO4; NH4HCO3; karbon aktif